Auditory stimulation with Mozart sonata k-448 and heavy metal music improves short-term memory in rats - Tonon do Amaral, Joice Anaize; Souza Faria, Rodolfo; Mourino de Faraco, Amanda; Mauad Coli, Ana Clara; Los Rios Leal, Joao Lucas de; de Souza e Silva, Marilia Pires; Oliveira Cortez, Paulo Jose; Leite, Iara Silva; Sartori, Cesar Renato; Valenti, Victor E.; Garner, David M.; Ribero Moreira, Dalmo Antonio; et al. (Open Science Journal, 2020)
OBJECTIVES: We aimed to assess the effect of both classical and heavy metal music on short-term and long-term memory. METHODS: Male rats were separated into three groups: Mozart (n=14), rats were exposed to Mozart´s K-448 piano sonata; Heavy Metal (n=15), rats were exposed to Psychosocial (band: Slipknot), and Control (n=12), rats were exposed to ambient sounds in an acoustically isolated room. The animals were exposed to the music for 8 hours per day, between 10:00 pm to 06:00 am, with an intensity of 50-75 dB, for 61 consecutive days. Twenty-four hours after the final day of adjustment to the enclosure the animals were individually exposed for 5 minutes in the enclosure to explore two identical objects. Ninety minutes after the object recognition training session, the animals were submitted to the short-term memory test and twenty-eight days after the object recognition training session, the animals were submitted to a long-term memory test. RESULTS: There was no modification amongst the three groups during the object recognition training. Regarding the short-term memory test both Mozart (U=33.00, p=0.016, FDR-corrected) and Heavy Metal (U=44.00, p=0.033, FDR-corrected) groups revealed a higher percentage value of significance compared to the control group. In contrast, there was no significant change in relation to the long-term memory test. CONCLUSION: Mozart Sonata K-448 and heavy metal music achieved beneficial effects on the short-term memory in rats.